Effects of Heliotropium strigosum and Trapa bicornis in hyperactive gut disorders (Bangladesh Journal of Pharmacology, 2017)
The current study was aimed to investigate the extracts from Heliotropium strigosum and Trapa bicornis phytochemically for various constituents and pharmacologically for gastro-intestinal disorders. Phytochemical analysis indicated the presence of alkaloids, flavonoids, glycosides and tannins in both the extracts. In castor oil-induced diarrhea, H. strigosum and T. bicornis, at 100-1000 mg/kg dose provided protection of 10-83% and 14-76% respectively. In isolated rabbit jejunum preparations, T. bicornis (0.01-5 mg/mL) relaxed the spontaneous and K+ (80 mM)-induced contractions with EC50 values of 1.2 mg/mL and 2.6 mg/mL respectively, suggesting that spasmolytic effect was possibly mediated through calcium channel blockade. This was further authenticated when pretreatment of tissues with T. bicornis (1-5 mg/mL) caused rightward shift of Ca++ concentrationresponse curves, similar to verapamil. In acute toxicity test, both extracts were safe up to 10 g/kg dose. These results indicated the usefulness of H. strigosum and T. bicornis in the treatment of hyperactive gut disorders.